2019
DOI: 10.3889/oamjms.2019.814
|View full text |Cite
|
Sign up to set email alerts
|

Elbow Fracture in Children at Saiful Anwar General Hospital, Nine Years Experiences

Abstract: AIM: The frequency, incidence, and types of fracture of the elbow are different between children and adult. The epidemiology of elbow fracture in children has been the subject of a limited number of studies. This study aims to observe the pattern of elbow fractures in children 18 years of age and younger, during a nine years period. METHODS: This is a retrospective study about elbow fracture cases in children 18 years old and younger treated in Saiful Anwar General Hospital Malang in the period of June 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Supracondylar humerus fractures are one of the most common injuries in childhood and adolescence with an incidence of 14% [ 1 ]. In the elbow joint, supracondylar humerus fractures account for more than two-thirds of all injuries [ 2 , 3 ] and occur most frequently between the age of 5 and 7 years [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Supracondylar humerus fractures are one of the most common injuries in childhood and adolescence with an incidence of 14% [ 1 ]. In the elbow joint, supracondylar humerus fractures account for more than two-thirds of all injuries [ 2 , 3 ] and occur most frequently between the age of 5 and 7 years [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…A 2013 Iranian study identified 8.1 ± 2.31 years old as the average age for all pediatric elbow fractures[ 25 ]. Similarly, an Indonesian study collecting data between 2009 to 2018 found the average age for all pediatric elbow fractures at 7.3 years[ 26 ]. In the American patient databases used, we did not observe any large age shifts from previous generations or for non-Western countries.…”
Section: Discussionmentioning
confidence: 99%
“…Lateral humeral condyle fractures account for 9.6–22.3% of all elbow fractures [ 1 , 2 , 4 , 5 , 6 , 7 , 11 , 12 , 13 , 14 ]. The majority (63–67.4%) of pediatric patients are male [ 8 , 9 , 13 , 14 , 15 ]. Most lateral humeral condyle fractures are seen between the ages of four and ten, but cases as early as 1.9 years have been reported [ 5 , 6 , 7 , 8 , 9 , 11 , 13 , 16 , 17 ].…”
Section: Epidemiologymentioning
confidence: 99%